In-hospital mortality and organ failure after open and endovascular thoraco-abdominal aortic surgery can be predicted by increased levels of circulating dipeptidyl peptidase 3. (25th November 2020) - Gombert, Alexander; Barbati, Mohammad; Kotelis, Drosos; Simon, Tim-Philipp; Breuer, Thomas; Hartmann, Oliver; Santos, Karine; Bergmann, Deborah; Schulte, Janin; Marx, Gernot; Jacobs, Michael; Stoppe, Christian
Abstract:  : OBJECTIVES: Endovascular and open thoraco-abdominal aortic aneurysm (TAAA) repair is associated with specific complications. Circulating dipeptidyl peptidase 3 (cDPP3) is a novel biomarker that shows a strong association with organ failure which has not been assessed in surgical settings. Therefore, the objective of this study was to assess the prognostic capabilities of cDPP3 for predicting patient survival and organ failure following open and endovascular TAAA repair. METHODS: Thirty-three patients undergoing TAAA repair were assessed in this prospective observational single-centre study. cDPP3 levels were serially measured perioperatively until 72 h after admission to the intensive care unit (ICU). In-hospital mortality and any organ failure were the clinical end points. RESULTS: Postoperative organ failure was detected in 17 patients (51.5%), and 6 patients died after surgery (18.2%). At 12 h after admission to the ICU, cDPP3 levels were significantly increased in patients who died or developed organ failure ( P  < 0.001). cDPP3 levels after surgery demonstrated a remarkable predictive accuracy for in-hospital mortality [12 h area under the receiver operating characteristic curve (AUC): 0.907 ( P  < 0.001), 24 h AUC: 0.815 ( P  = 0.016), 48 h AUC: 0.914 ( P  = 0.003)] and the development of organ failure [12 h AUC: 0.882 ( P  < 0.001), 24 h AUC: 0.850 ( P  < 0.001), 48 h AUC: 0.846 ( P  < 0.001)]. Additionally, a significant correlation between cDPP3, the sequential organ failure assessment score and procalcitonin, C-reactive protein and interleukin-6 levels ( P  < 0.001, P  < 0.001, P  = 0.011, P  = 0.007, respectively) based on all available measurements and time points was observed. CONCLUSIONS: The present findings highlight the role of cDPP3 as an early, highly specific postoperative biomarker for prediction of in-hospital mortality and organ failure after TAAA repair.